Clinical Characteristics and the Long-Term Post-recovery Manifestations of the COVID-19 Patients—A Prospective Multicenter Cross-Sectional Study - Mohiuddin Chowdhury, Abu Taiub Mohammed; Karim, Md Rezaul; Ali, Md. Ahasan; Islam, Jahirul; Li, Yarui; He, Shuixiang (Frontiers in Medicine, 2021)
Objective: Coronavirus disease 2019 (COVID-19) or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a global issue. In addition to managing acute cases, post-COVID-19 persisting symptoms/complaints and different hematological values are of great concern. These have an impact on the patient's well-being and are yet to be evaluated. Therefore, clinical and primary diagnosis based on routine laboratory findings bears high importance during the initial period of COVID-19, especially in regions with fewer diagnostic facilities. Methods: Clinical information and associated complaints of the COVID-19 illness confirmed by reverse transcription-polymerase chain reaction (RT-PCR) were collected directly from the patients. Regular follow-ups were obtained on the phone every 2 weeks following recovery for 20 weeks. Initial hematological and radiology findings of the hospitalized patients except for intensive care unit (ICU) and high dependency units (HDUs) and a follow-up evaluation after 4 weeks following recovery were analyzed. Results: The post-COVID-19 persisting symptoms/complaints were found among 21.4% of symptomatic patients, which persisted for ≥20 weeks and had a significant relationship with the duration of COVID-19 illness and the existing comorbidity (p < 0.05). Post-COVID-19 primary type 2 diabetes mellitus (DM, 0.64%) and hypertension (HTN, 1.28%) and unstable DM (54.55%) and HTN (34.78%) to the pre-existing diabetic and hypertensive patients were observed. Post-recovery remarkable changes in the laboratory values included leukocytosis (16.1%), lymphocytosis (14.5%), and an increased prothrombin time (PT, 25.8%). Abnormalities in the D-dimer, serum ferritin, hemoglobin, and erythrocyte sedimentation rate (ESR) levels were present to an extent. Laboratory findings like chest X-ray, ESR, white blood cell (WBC) count, lymphocyte count, C-reactive protein (CRP), serum glutamic pyruvic transaminase (SGPT), serum ferritin, PT, D-dimer, and serum creatinine are important markers for the diagnosis and prognosis of COVID-19 illness (p < 0.05). Conclusion: Post-COVID-19 persisting symptoms and the changes in the laboratory values need to be considered with importance and as a routine clinical measure. Post-COVID-19 periodic follow-up for evaluating the patient's physical condition and the biochemical values should be scheduled with care and managed accordingly to prevent future comorbidity in patients with the post-COVID-19 syndrome.